New findings on Eocene stratigraphy and paleogeography of Elazi? area - Türkmen, Ibrahim; Inceöz, Murat; Aksoy, Ercan; Kaya, Meral (My University, 2001)
Tertiary deposits of Neotethys widespreadly outcrop in the eastern part of the Taurus Orogenic Belt. It has been declared that there is an unconformity between the Upper Paleocene-Lower Eocene Seske Formation and Middle Eocene-Oligocene Kirkgei?t Formation in all the previous investigations in the Elazi? area. In this study, stratigraphic sections involving these two units, which are characterized by marine facies, have been measured and 22 benthic and planktic foraminiferal genera and some of their species were identified. These are: Coskinolina, Textularia, Alveolina, Acarinina, Morozovella, Globigerina, Planorbulina, Fabiania, Eorupertia, Sphaerogypsina, Daviesina, Cuvillierina, Kathina, Lockhartia, Miscellanea, Assilina, Nummulites, Operculina, Ranikothalia, Discocyclina, Orbitoclypeus and Asterocyclina. Both field data and sedimentological-paleontological data indicate that there is no unconfirmity between Seske and Kirkgei?t formations which are characterized interbedded clastic and carbonate rocks. However, in some outcrops such as those in the northern and southern vicinity of Elazi?, Middle Eocene-Oligocene Kirkge? Formation rests unconformably on pre-Tertiary magmatic and metamorphic units, without Upper Paleocene-Lower Eocene Seske Formation. This stratigraphic position indicates that the extent of the Neotethys have been controlled by the tectonic and topographic features of the region in Eocene. In addition, some parts of this area were under subarial conditions in Late Paleocene and Early Eocene period. Facies relationship in the measured sections also supports this interpretation.
Elazi? yöresinin Eosen stratigrafisi ve paleoco?rafyasi ile ilgili yeni bulgular
Keywords: Elazi?; Eocene stratigraphy; Paleogeography